Alcohol Levels In Gaplek Tape on Yeast Dosage - Destri Handayani; Purwati widiyanto (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Abstract Background: Gaplek is one of the cassava preservation products. Gaplek can be processed into tape called cassava tape. Dosage of yeast in the manufacture of cassava tape increases the alcohol content in cassava tape. Objectives: To determine the alcohol content in cassava tape after the addition of yeast with various doses. Research Metodes: This research method is experimental. For this type of research is true experimental. The sample used is cassava. Findings: Based on the results of the alcohol content above, it can be seen that the highest alcohol content was at a yeast dose of 1.10%, namely 14.08% and decreased at a yeast dose of 1.35% with an alcohol content of 11.83%. After getting the results of the alcohol content, the data were processed using linear regression equations and obtained the equation Y=7.181x+4.846 with the determinant correlation coefficient R2 = 0.747 so that the correlation was 0.8643 which means it has a very strong correlation or correlation coefficient. Conclusion: The alcohol content in the tape increased with the addition of the yeast dose, where the highest level of 14,085 was obtained by adding 1.10% yeast into the cassava, but the yeast content decreased when more yeast was added. Keywords: Gaplek;Alcohol Level; Yeast dose